Does Good Financial Performance Mean Good Financial Intermediation in China? - Feyzioglu, Tarhan (IMF Working Papers; Working Paper ;, 2009)
Chinese banks generate large profits and have relatively low nonperforming loans. However, good financial performance does not, in itself, guarantee that banks efficiently intermediate the economy's financial resources. This paper first examines how efficient Chinese banks are in financial intermediation, using the stochastic production frontier approach. Quality of loans are controlled for by focusing on net loans and correcting for nonperforming loans; Hong Kong SAR banks are included in the sample to have a more universally representative production frontier. The results suggest that Chinese banks indeed became more efficient during 2001-07. Nevertheless, a majority of banks remain quite inefficient, including several large state owned banks and many city banks. Large banks tend to hoard deposits and operate beyond the point of diminishing returns to scale, while smaller banks operate at increasing returns to scale. This suggests that reallocating deposits from large to smaller banks would increase overall efficiency. The paper finds no significant correlation between bank efficiency and profitability. Possible factors leading to large profits in the banking system, despite wide-spread inefficiencies, are low deposit interest rates, large interest margins, and high market concentration. Moving to indirect monetary policy and deepening capital markets to channel some of the savings to productive investment would help improve the efficiency of financial intermediation. This may spur loan growth, however, which will need to be handled with monetary policy and regulatory/supervisory tools.